2017
DOI: 10.1021/acs.jmedchem.7b01293
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small-Molecule Inhibitors of Ubiquitin Specific Protease 7 (USP7) Using Integrated NMR and in Silico Techniques

Abstract: USP7 is a deubiquitinase implicated in destabilizing the tumor suppressor p53, and for this reason it has gained increasing attention as a potential oncology target for small molecule inhibitors. Herein we describe the biophysical, biochemical, and computational approaches that led to the identification of 4-(2-aminopyridin-3-yl)phenol compounds described by Kategaya ( Nature 2017 , 550 , 534 - 538 ) as specific inhibitors of USP7. Fragment based lead discovery (FBLD) by NMR combined with virtual screening and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…Several inhibitors targeting USP7/HAUSP were screened and exhibited anti‐tumor effect . Chauhan et al discovered that P5091 exhibited specific and selective deubiquitylating activity against USP7 and did not inhibit other DUBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several inhibitors targeting USP7/HAUSP were screened and exhibited anti‐tumor effect . Chauhan et al discovered that P5091 exhibited specific and selective deubiquitylating activity against USP7 and did not inhibit other DUBs.…”
Section: Introductionmentioning
confidence: 99%
“…Several inhibitors targeting USP7/HAUSP were screened and exhibited anti-tumor effect. 16,25,[28][29][30][31][32] Chauhan et al 25 discovered that P5091 exhibited specific and selective deubiquitylating activity against USP7 and did not inhibit other DUBs. P5091 significantly inhibited HCT116 (wt) cells growth; conversely, a slight effect on HCT116 USP7 −/− cells, which suggested that P5091 specifically targeted USP7.…”
mentioning
confidence: 99%
“…Medicinal chemistry optimization of a fragment yielded the small molecules GNE6640 (20) and GNE6776 (21) shown in Figure 2. This class of allosteric inhibitors has been demonstrated to bind to the 'palm' region of the USP7 catalytic domain thereby impeding ubiquitin binding (orange, Figure 2B) [99,100]. NMR-based saturation transfer difference (STD) experiments showed that these compounds bind to a novel functional site 12 Å away from the catalytic cysteine residue [100].…”
Section: Usp7mentioning
confidence: 99%
“…This class of allosteric inhibitors has been demonstrated to bind to the 'palm' region of the USP7 catalytic domain thereby impeding ubiquitin binding (orange, Figure 2B) [99,100]. NMR-based saturation transfer difference (STD) experiments showed that these compounds bind to a novel functional site 12 Å away from the catalytic cysteine residue [100]. These molecules potently inhibited the activity of USP7 (IC50 values of 1.34 μM and 0.75 μM, respectively) and did not inhibit the activity of a panel of 36 DUBs at concentrations of 100 μM, which is convincing evidence of high target selectivity [99].…”
Section: Usp7mentioning
confidence: 99%
“…For example, nuclear magnetic resonance‐based screening has directed to the development of GNE‐6640 and GNE‐6776. Both compounds can non‐covalently target and selectively inhibit USP7 relative to 36 other deubiquitinases and induce cell death with significant impact on cellular USP7, MDM2, and p53 signalling pathways . Recently a new class of USP7 inhibitors has been identified based on P5091 and P22077 as the lead compounds.…”
Section: Ubiquitin Specific Protease 7 (Usp7)mentioning
confidence: 99%